Changes in the structure of the microbial community within the phycospheric microenvironment and potential biogeochemical effects induced in the demise stage of green tides caused by Ulva prolifera - Liu, Xiaoxue; Zang, Yu; Fan, Shiliang; Miao, Xiaoxiang; Fu, Mingzhu; Ma, Xiaojun; Li, Mei; Zhang, Xuelei; Wang, Zongling; Xiao, Jie (Frontiers in Microbiology, 2024)
Green tides caused by Ulva prolifera occur annually in the Yellow Sea of China, and the massive amount of biomass decomposing during the demise stage of this green tide has deleterious ecological effects. Although microorganisms are considered key factors influencing algal bloom demise, an understanding of the microbial-algae interactions within the phycospheric microenvironment during this process is still lacking. Here, we focused on the variations in phycospheric microbial communities during the late stage of the green tide in three typically affected areas of the Yellow Sea via metagenomic sequencing analysis. In total, 16.9 million reads obtained from 18 metagenome samples were incorporated into the assembled contigs (13.4 Gbp). The phycosphere microbial community composition and diversity changed visibly during the demise of U. prolifera. The abundances of algae-lysing bacteria, Flavobacteriaceae at the family level and Alteromonas, Maribacter, and Vibrio at the genus level increased significantly in the phycosphere. In addition, the levels of glycoside hydrolases (GHs) and polysaccharide lyases (PLs) enzymes, which decompose U. prolifera polysaccharides in the phycosphere, were greater. Therefore, the degradation of algal polysaccharides can increase the efficiency of carbon metabolism pathways in the phycospheric microenvironment. Most of the genes detected in the phycosphere, especially norC, nrfA, and nasA, were associated with nitrogen metabolism pathways and showed dynamics related to the demise of the large amount of organic matter released by a green tide. Therefore, the demise of green tide algae may affect the potential carbon and nitrogen cycles of the phycospheric microenvironment by driving changes in the structure and diversity of microbial communities. Our research provides a novel perspective to better understand the ecological impact of U. prolifera during the green tide demise stage.